Evaluating the Potential for Harmonized Prediction and Comparison of Disposal‐Stage Greenhouse Gas Emissions for Biomaterial Products. (5th May 2016) - Glew, David; Stringer, Lindsay C.; Acquaye, Adolf; McQueen‐Mason, Simon
Summary: The carbon footprint (CF) of biofuels and biomaterials is a barrier to their acceptance, yet the greenhouse gas emissions associated with disposing of biomaterials are frequently omitted from analyses. This article investigates whether harmonization is appropriate for calculating the importance of biomaterials' disposal. This research shows that disposal stages could double a biomaterial's CF, or reduce it to the point that it could claim to be zero carbon. Incineration with combined heat and power coupled with on‐site energy production in the biorefinery are identified as prerequisites to being zero carbon. The article assesses the current UK waste infrastructure's ability to support a low‐carbon bio‐based future economy, and finds that presently it only achieves marginal net reductions when compared to landfill and so cannot be said to support low‐carbon biomaterials, though the article challenges the polluter pays principle where low‐carbon disposal infrastructure are not available. Reuse and recycling are shown to have the potential to offset all the emissions caused by landfill of biomaterials. However, the savings are not so great as to offset the biomaterial's upstream emissions. The study explores the ability to overcome the barriers to incorporating disposal into life cycle assessment while identifying limitations of using harmonization as an assessment method. Specifically, data availability and industry consensus are flagged as major barriers. The study also uses sensitivity analysis to investigate the influence of methodological choices, such as allowing additional reuse and recycling stages, classifying biomaterials into different types, and choosing between opposing allocation methods.